2017
DOI: 10.24349/acarologia/20174200
|View full text |Cite
|
Sign up to set email alerts
|

Ants as predators of the Spinose Ear Tick, Otobius megnini (Dugès) in Sri Lanka

Abstract: Many pathogens, parasitoids and predators have been documented as natural enemies of ticks, but their impact on tick populations are rarely evaluated. Here, we report the predatory behaviour of ants on the spinose ear tick, Otobius megnini. Ticks were collected from the ear canal of stabled horses in Nuwara Eliya and were brought to the laboratory. Eggs, unfed and engorged larvae, engorged nymphs and adults were naturally exposed to ants under laboratory conditions and the predatory behaviour of the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…The level of interest of L. alienus in the eggs was closely related to the tick species, and the results revealed that the eggs of Hyalomma species, particularly H. excavatum , were preferred more by the ant compared to the eggs of R. bursa . Similar variability has been clearly demonstrated previously regarding different species of ticks and ants 7 , 13 , 14 . However, presenting the eggs to the ants after the dewaxing process resulted in both more significant interest in the eggs and a decrease in the differences between the eggs of the tick species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The level of interest of L. alienus in the eggs was closely related to the tick species, and the results revealed that the eggs of Hyalomma species, particularly H. excavatum , were preferred more by the ant compared to the eggs of R. bursa . Similar variability has been clearly demonstrated previously regarding different species of ticks and ants 7 , 13 , 14 . However, presenting the eggs to the ants after the dewaxing process resulted in both more significant interest in the eggs and a decrease in the differences between the eggs of the tick species.…”
Section: Discussionsupporting
confidence: 89%
“…Ant predation has been examined in all developmental stages of ticks, but the proportion of the studies based on the eggs is relatively low compared to the other stages 2 . In an egg-based study, the eggs of O. megnini , the spinose ear tick, were supplied to five different ant species, and of those, Tapinoma melanocephalum was the only species that fed on the eggs 7 . Conflicting results have been reported from the studies 13 , 14 carried out to determine the predatory effects of ant species Pheidole megacephala on the eggs of Boophilus ( Rhipicephalus ) microplus 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these ants occasionally target ticks as their main food source but are natural predators of tick species including Argas miniatus [102], R. microplus, and R. annulatus [102], O. megnini, and Ornithodorus moubata [53]. Five ant species, Tapinoma melanocephalum, two species of Monomorium, one species of Pheidole, and one species of Crematogaster feed on eggs fed and unfed larvae and adults of O. megnini (Figure 5) [103]. Among these, T. melanocephalum is the best predator as it feeds all free-living stages (eggs and adults) [103].…”
Section: Control Methodsmentioning
confidence: 99%
“…Several studies have also revealed several possible tick vectors other than H. longicornis (Table 1). Prior to the recent Australian T. orientalis outbreak, H. bancrofti and H. humerosa [103][104][105][106] were found to be more competent and efficient vectors compared to H. longicornis under experimental conditions, although it is noted that the H. humerosa used in these studies were latterly believed to be H. bremneri [106,107]. These studies employed the 'Warwick stock' of T. orientalis which is of the Buffeli genotype.…”
Section: Vectors Of T Orientalismentioning
confidence: 99%
See 1 more Smart Citation